2019
DOI: 10.1590/0037-8682-0290-2019
|View full text |Cite
|
Sign up to set email alerts
|

Phage Therapy as an Approach to Control Salmonella enterica serotype Enteritidis Infection in Mice

Abstract: Introduction: Salmonella enterica serotype Enteritidis (S. Enteritidis) is a cause of food-borne human illness. Given the prevalence of antibiotic resistance of Salmonella Enteritidis and the lack of antibiotic efficacy in future years, its replacement with other agents is necessary. One of the most useful agents is bacteriophages. Methods: S. Enteritidis was identified using a multiplex polymerase chain reaction assay. The effective bacteriophages were isolated from hospital wastewater samples. The effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
1
9
0
2
Order By: Relevance
“…Ideally, the therapeutic evaluation in vivo model is also needed for candidates for phage therapy. Previous studies have shown the bacterial infection can be cured by treatment with phage in experimentally or naturally infected animals ( 35 , 57 ). Thus, we carried out the evaluation of the therapeutic efficacy of SHWT1 in vivo infection test.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the therapeutic evaluation in vivo model is also needed for candidates for phage therapy. Previous studies have shown the bacterial infection can be cured by treatment with phage in experimentally or naturally infected animals ( 35 , 57 ). Thus, we carried out the evaluation of the therapeutic efficacy of SHWT1 in vivo infection test.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many papers have been published recently which described bacteriophages that might be used in phage therapy against Salmonella . They include reports on characterization of previously unknown bacteriophages having the potential for use in phage therapy [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], experimental studies with bacteriophages applied to poultry [ 21 , 22 , 23 , 24 , 25 , 26 ], and the use of bacteriophages in experimental phage therapy in mouse [ 27 , 28 , 29 , 30 ] or pig [ 31 ] models. Although promising results were obtained in these studies, and economic analyses have been performed to assess costs and benefits of the use of phage therapy for the control of Salmonella in poultry [ 9 , 32 ], it is evident that the host range of the vast majority of Salmonella phages is restricted to specific strains or serovars.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on the ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter cloacae) (Debarbieux et al, 2010;Kumari et al, 2010;Chhibber et al, 2013;Jeon et al, 2016), a group of organisms designated by the World Health Organization as serious threats to global health based on high rates of multidrug resistance (Tacconelli et al, 2017). Animal studies have also used phage therapy to treat organisms such as Escherichia coli (Schneider et al, 2018), Salmonella enterica (Dallal et al, 2019), Vibrio cholerae (Bhandare et al, 2019), Mycobacterium ulcerans (Trigo et al, 2013), and Burkholderia pseudomallei (Guang-Han et al, 2016). Meanwhile, the relationship between antibiotic resistance and phage resistance (or sensitivity) in these organisms is a complex one.…”
Section: Bacteria and Phages Employed In Animal Modelsmentioning
confidence: 99%
“…Other studies on infections of the lower gastrointestinal tract have examined enteric pathogens such as S. enterica and V. parahaemolyticus. A study of S. enterica serovar enteritidis in mice found that oral phages administered at an MOI of 10 1 day after gavage with the bacteria showed no signs of infection, and no bacteria were isolated from the liver; mice not administered phages all died at the end of the experiment and exhibited clear liver pathology associated with recovered Salmonella isolates (Dallal et al, 2019). In a model of V. parahaemolyticus enteritis, mortality rates were twice as high in control mice compared to mice treated intraperitoneally with phages (Jun et al, 2014).…”
Section: Diarrheal Infectionsmentioning
confidence: 99%